2015
DOI: 10.1016/j.sandf.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Near-field ground thermal response to heating of a geothermal energy pile: Observations from a field test

Abstract: Field observations from a heating test conducted on a geothermal energy pile, containing two Osterberg cells, installed in a dense sandy material are reported. An instrumented pile and two boreholes were installed for this purpose. The pile was heated for various time intervals and the ground heat response was observed via thermocouples installed at various depths in the two boreholes. A time lag in the diffused heat wavefront arrival was consistently observed in the borehole farthest from the heat source (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…Temperature changes can induce volumetric changes of an energy pile and can potentially affect the interaction between the energy pile and the soil. Recent studies on field scale energy piles have assessed their thermal response mostly when they are subjected to monotonic heating (Laloui et al, 2006;Bourne-Webb et al, 2009;Akrouch et al, 2014;Mimouni, 2014;Mimouni and Laloui, 2015;Wang et al, 2015;Sutman et al, 2015) or under normal seasonal heat pump operation (Brandl 2006;McCartney 2012, 2015;McCartney and Murphy 2017). The thermal response of field scale energy piles subjected to daily cyclic temperatures under intermittent operations of a heat pump with natural ground thermal recovery has only recently started to receive interest (Faizal et al, 2016), and practically no assessments have been reported in the literature for daily cyclic temperatures resulting from forced ground thermal recharging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature changes can induce volumetric changes of an energy pile and can potentially affect the interaction between the energy pile and the soil. Recent studies on field scale energy piles have assessed their thermal response mostly when they are subjected to monotonic heating (Laloui et al, 2006;Bourne-Webb et al, 2009;Akrouch et al, 2014;Mimouni, 2014;Mimouni and Laloui, 2015;Wang et al, 2015;Sutman et al, 2015) or under normal seasonal heat pump operation (Brandl 2006;McCartney 2012, 2015;McCartney and Murphy 2017). The thermal response of field scale energy piles subjected to daily cyclic temperatures under intermittent operations of a heat pump with natural ground thermal recovery has only recently started to receive interest (Faizal et al, 2016), and practically no assessments have been reported in the literature for daily cyclic temperatures resulting from forced ground thermal recharging.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most previous studies on field scale energy piles have assessed their axial thermal responses under monotonic increases or decreases in temperature (Bourne-Webb et al, 2009;Akrouch et al, 2015; or under actual heat pump operation McCartney and Murphy, 2017), both of which do not permit a simple evaluation of the long-term effects of cyclic heating and cooling. Further, consideration of radial strains in energy piles are limited to a few studies (Laloui et al, 2006;Mimouni, 2014;Mimouni and Laloui, 2015;Wang et al, 2015, Wang, 2017. An assessment of the radial thermal response of field-scale energy piles will clarify if lateral expansion/contraction of the pile could cause pile and soil deformations under monotonic and cyclic temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to help clarify the role of different variables (soil type, saturation conditions, cyclic loading, restraint at the head or toe of the energy pile), the results from the centrifuge modelling are also useful to calibrate and validate numerical simulations. Wang et al (2012bWang et al ( , 2015) used a coupled thermo-hydro-mechanical model to evaluate the thermal axial stresses and strains in the energy pile results presented by Stewart and McCartney (2014). A good match between the calibrated model and the experimental results was obtained when the model was performed using model-scale results.…”
Section: Evaluation Of Soil-structure Interaction In Centrifuge-scalementioning
confidence: 99%
“…Finally, thermomechanical effects that are induced on the heat exchanger constitute an emergent and promising field of investigation [47,48]. Experimental research is very active as well, on each and every level, providing empirical support and validation to both analytical and numerical models [10,49].Despite a number of encouraging results, even in the numerical modelling of GHE a number of issues still need to be addressed [10,12,50]. In this paper we are mostly concerned with the assessment of variable ground surface temperatures.…”
mentioning
confidence: 99%
“…Finally, thermomechanical effects that are induced on the heat exchanger constitute an emergent and promising field of investigation [47,48]. Experimental research is very active as well, on each and every level, providing empirical support and validation to both analytical and numerical models [10,49].…”
mentioning
confidence: 99%